Species-level ichthyoplankton dynamics for 97 fishes in two major river basins of the Amazon using quantitative metabarcoding - Mariac C. (2021)
The two years of larvae collection in the Marañón and Ucayali rivers were financed by the Concejo Nacional de Ciencia y Tecnología (CONCYTEC) of Peru, who through the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT), project 088-2014-FONDECYT-DE. The LMI EDIA and UMR DIADE financed the metabarcoding analyses. The authors acknowledge the IRD itrop HPC (South Green Platform) at IRD Montpellier for providing HPC resources that contributed to the research results reported within this paper ( https://bioinfo.ird.fr/ - http://www.southgreen.fr ). We are also grateful to Domingo García for his assistance during field work. We are also grateful to Juan José Palacios Vega (IIAP) for the elaboration of Figure 1 .